2021
DOI: 10.3390/foods10071564
|View full text |Cite
|
Sign up to set email alerts
|

Natural Bioactive Compounds from Food Waste: Toxicity and Safety Concerns

Abstract: Although synthetic bioactive compounds are approved in many countries for food applications, they are becoming less and less welcome by consumers. Therefore, there has been an increasing interest in replacing these synthetic compounds by natural bioactive compounds. These natural compounds can be used as food additives to maintain the food quality, food safety and appeal, and as food supplements or nutraceuticals to correct nutritional deficiencies, maintain a suitable intake of nutrients, or to support physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(58 citation statements)
references
References 119 publications
0
58
0
Order By: Relevance
“…Residues from the agri-food industry, i.e., by-products and waste, are valuable sources for the recovery of bioactive compounds, among which polyphenols and fibre are applicable in the food industry as natural functional food additives and ingredients. In fact, recent studies have reported that these compounds possess health-promoting effects, including antioxidant, anti-inflammatory, and immunomodulatory properties [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Residues from the agri-food industry, i.e., by-products and waste, are valuable sources for the recovery of bioactive compounds, among which polyphenols and fibre are applicable in the food industry as natural functional food additives and ingredients. In fact, recent studies have reported that these compounds possess health-promoting effects, including antioxidant, anti-inflammatory, and immunomodulatory properties [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The growing demand for foods with beneficial effects on health, while contributing to the sustainable use of natural resources, stimulates the use of by-products to obtain bioactive compounds (Vilas-Boas et al, 2021), which have multiple applications in food, acting as antimicrobials, antioxidants, natural dyes, fortifying ingredients, texture modifiers, and others (Veneziani et al, 2017).…”
Section: Potential Applications Of Bioactive Compounds Recovered From Waste and By-productsmentioning
confidence: 99%
“…Proteins, carbohydrates, and lipids, which are potential ingredients for the manufacture of enzymes, gelatin, collagen, and other bioactive compounds, are known to be present in discarded and underutilized by-products [ 48 ]. This signifies that the extraction products are the potential raw materials for food additives, functional foods, nutraceuticals, pharmaceuticals, and, more crucially, bio-packaging products [ 49 ]. Kringel’s colleagues reviewed starch extraction from roots, tubers, pulses, pseudo-cereals, and other unconventional sources [ 50 ].…”
Section: Extraction Of Starchmentioning
confidence: 99%